Integrating Business Process Reengineering and Risk-Based Costing: Evidence from an Automotive Battery Manufacturer - Ali Abdul-Hussein Hani Al-Zameli (Review of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to evaluate how the integration of Business Process Reengineering (BPR) and Risk-Based Costing (RBC) can improve both operational and resource efficiency in manufacturing. The research focuses on the General Company for Automotive and Equipment Manufacturing – Battery Factory, specifically on the 90 Ampere dry battery production process in 2024. Research methodology: The study adopts a mixed-method approach combining quantitative and descriptive analyses in an applied research design. The BPR method was used to identify inefficiencies and process waste within the main production line, while the RBC approach was employed to map and quantify risks influencing product cost in key manufacturing operations. Results: Findings revealed that the joint application of BPR and RBC significantly reduced production cycle times, material waste, and operational costs. The integrated approach also improved risk-adjusted resource allocation, demonstrating superior performance compared to implementing either method independently. Conclusions: The combination of BPR and RBC enhances efficiency, cost control, and risk management in manufacturing operations. The study recommends the adoption of this integrated approach across the company’s product lines and the enhancement of accounting and management information systems to ensure sustainability. Limitations: The research is limited to one factory and a single product type, which may restrict generalizability to other industries or products. Contribution: This study contributes to the development of integrated efficiency frameworks in industrial management, highlighting the synergistic potential of BPR and RBC in optimizing production and resource utilization.